2008
DOI: 10.1590/s0101-81752008000100001
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of Sotalia guianensis (Van Bénéden) in Pernambuco coastal waters, Brazil, and a further analysis of its reaction to boat traffic

Abstract: There is still little knowledge about the behavior of the estuarine dolphins and also the way they react to the presence of different types of vessels. The aim of the present study was twofold: to investigate the behavior of estuarine dolphins in four locations in Pernambuco, Brazil, and also their reaction to the presence of common types of nautical crafts. The data of this study resulted from 48 fieldtrips to each of the four localities studied (ports of Recife and Suape, and beaches of Bairro Novo and Pieda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
6
0
3
Order By: Relevance
“…The direction of vessel traffic must also be considered when studying interactions with cetaceans. In this study, as similarly reported by Araújo et al (2008), the vessels only passed through the area and spent a short time interacting with the dolphins. The distance from boats did not interfere in the surfacing pattern of the dolphins.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The direction of vessel traffic must also be considered when studying interactions with cetaceans. In this study, as similarly reported by Araújo et al (2008), the vessels only passed through the area and spent a short time interacting with the dolphins. The distance from boats did not interfere in the surfacing pattern of the dolphins.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, Araújo et al (2008) observed a predominance of neutral reactions to all types of boats. These authors suggested that the reactions were neutral because the speed and direction of the boats were constant.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Guiana dolphin populations are frequently exposed to human activities because they inhabit coastal areas (Borobia et al 1991). Mortality due to accidental ( e.g ., Di Beneditto 2003) and intentional catches (Sholl et al 2008), boat strikes ( e.g ., Van Bressem et al 2007), behavioral disturbances due to boat traffic ( e.g ., Araújo et al 2008), skin diseases ( e.g ., Van Bressen et al 2009), and high levels of persistent contaminants in tissues ( e.g ., Yogui et al 2003) are known threats to this species. Effective monitoring efforts that provide robust estimates of a set of population parameters are therefore a necessity.…”
mentioning
confidence: 99%